Assessment of sidewalk system in the University of Ibadan (2023)
Good pedestrian facilities support the ease, comfort and safety of pedestrians. A good pedestrian sidewalk requires a good surface condition with appropriate footpath width and surface quality. This study assessed pavement condition of sidewalks in the University of Ibadan using the Pavement Condition Index (PCI) method. PCI evaluates the surface condition of sidewalks based on distresses observed. The PCI ratings vary from 0 to 100, representing the worst and best surface conditions, respectively. Based on the regular use of sidewalks for access, eighteen major roads were selected within the University of Ibadan. A distress assessment survey was conducted on the roads to collect data on defective sidewalk pavements and their distress conditions. The sidewalks were mainly of two types: plain concrete and concrete slab. Average sidewalk width for fourteen of the roads was less than 1.5 m stipulated in highway design manuals. Sixty percent of the sidewalks were in good condition with PCI values greater than 70. The recurring defects on the plain concrete sidewalk included linear, edge and map cracking. Depression of slab units was the most severe defect on the concrete slap sidewalk. The PCI analysis was used to assess the surface conditions of sidewalks in the University of Ibadan. The results can be used to design maintenance activities to keep the sidewalk system in optimal operational function. Having and updating inventory of the sidewalk system will promote regular routine maintenance and encourage safe use of the system